The Effect of Schema-Based Premarital Education on Fear of Marriage and Coping Styles in Single Girls - Samaneh Mokhtari; Zahra Yousefi; Gholam Reza Manshaei (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2021)
Aim and Background: Today, marriage is not simply as past, and young people on the verge of marriage suffer from a fear or concern about marriage and its issues that related to cognitive distortions, maladaptive schemas and coping styles that individuals use against schemas. The aim of this study was to investigate the effect of schema-based premarital education on fear of marriage and coping styles in single girls in Isfahan. Methods and Materials: The present study was a quasi-experimental study with a pretest and posttest design with a control group. The statistical population of this study included student and single girls in Esfahan; The study sample consisted of 30 people who were selected by available sampling method and were randomly divided into two experimental groups (15 people) and control (15 people). Subjects in two stages of pre-test and post-test were Samiei, Yousefi and Neshat Doost (2014) and Young's Schemas Minds (2008). The experimental group received schema-based premarital education as a group during 15 sessions of 90 minutes, while the control group did not receive any training. Data were analyzed using descriptive statistics and univariate and multivariate analysis of covariance and SPSS software version 23. Findings: The results of comparison of the experimental group with the control group showed that the function of fear of marriage and coping styles was significantly different from the control group. In other hand, Schematic-based premarital education had a significant effect on fear of marriage and coping styles of single girls (p <0.05). Conclusions: In general, the results showed the effect of schema-based premarital education on fear of marriage and coping styles of single girls; and it can be used as an important and key intervention in the field of premarital. Also, the results of this research can be used by family and marriage counselors.